A validated LC‐MS/MS method for the determination of senkyunolide I in dog plasma and its application to a pharmacokinetic and bioavailability studies. (16th January 2018) - Li, Jin‐Qi; Wang, Jia‐Feng; Li, Jie; Zhang, Shu‐han; He, Dan; Tong, Rong‐Sheng; She, Shu‐Ya
Abstract: Senkyunolide I is one of the major bioactive components in the herbal medicine Ligusticum chuanxiong. The aim of this study was to develop and validate a fast, simple and sensitive LC‐MS/MS method for the determination of senkyunolide I in dog plasma. The plasma samples were processed with acetonitrile and separated on a Waters Acquity UPLC BEH C18 column (50 × 2.1 mm, 1.7 μm). The mobile phase consisted of 0.1% formic acid aqueous and acetonitrile was delivered at a flow rate of 0.3 mL min −1 . The detection was achieved in the positive selected reaction monitoring mode with precursor‐to‐product transitions at m/z 225.1 → 161.1 for senkyunolide I and at m/z 349.1 → 305.1 for an internal standard. The assay was linear over the tested concentration range, from 0.5 ng mL −1 to 1000 ng mL −1, with a correlation coefficient >0.9992. The mean extraction recovery from dog plasma was within the range of 85.78–93.25%, while the matrix effect of the analyte was within the range of 98.23–108.89%. The intra‐ and inter‐day precisions (RSD) were <12.12% and the accuracy (RR) ranged from 98.89% to 104.24%. The validated assay was successfully applied to pharmacokinetic and bioavailability studies of senkyunolide I in dogs. The results demonstrated that (a) senkyunolide I showed short elimination half‐life (<1 h) in dog, (b) its oral bioavailability was >40% and (c) senkyunolide I showed dose‐independent pharmacokinetic profiles in dog plasma over the dose range of 1–50 mg kg −1 .